OTENTISITAS SUNNAH DAN KEDUDUKANNYA DALAM LEGISLASI HUKUM ISLAM - Nur Kholis Hauqola (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2014)
This paper aims to discover the truth of the authenticity of the Sunnah as the basis of Islamic law legislation. The problem lies on the